AN ANALYSIS OF COMMISSIVE SPEECH ACTS USED BY THE MAIN CHARACTERS IN WOMEN-CENTRIC MOVIES - Ashfiya, Hamadah; Degaf, Agwin (Sanata Dharma University, 2023)
This study explores the usage of commissive speech acts in the women-centric movies